Pemberdayaan Ekonomi Masjid Dalam Upaya Meningkatkan Kesejahteraan Jamaah - Nadiyah Rahmadani; Nurfaradilla Juliana; Kyra Khairunnisa; Habib Muhammad Syamil; Bulan Reta Aziza; Luthfiah Nur Falaqih (Yayasan Haiah Nusratul Islam, 2026)
The mosque as an Islamic religious institution has enormous economic potential that has not yet been maximally optimized. This study aims to analyze mosque economic empowerment strategies, identify successfully implemented models, and measure their impact on the welfare of congregants and surrounding communities. The research method employs a descriptive qualitative approach with case studies conducted at ten major mosques in Indonesia that have implemented productive economic programs. Data were collected through in-depth interviews, participant observation, and document analysis. The results indicate that mosques that have successfully empowered the community's economy apply a combination of programs including: mosque-based business units (cooperatives, minimarkets, and assisted MSMEs), professional management of zakat, infaq, and sadaqah (ZIS), and the development of productive waqf. Key success factors include visionary takmir leadership, financial management transparency, active congregation participation, and synergy with Islamic financial institutions. The mosque economic empowerment program has been proven to reduce the poverty rate in the mosque's surrounding community by up to 18.7% and increase the average income of congregants by 23.4% over a three-year period. This study affirms that mosques can transform into holistic centers of Islamic economic civilization when managed with professional management based on sharia values.